Generation of a squeezed state at 1.55 μm with periodically poled LiNbO3 - 刘勤 冯晋霞 李宏 焦月春 张宽收 (中国物理B：英文版, 2012)
We report on the generation of a squeezing vacuum at 1.55 μm using an optical parametric amplifier based on periodically poled LiNbO 3.Using three specifically designed narrow linewidth mode cleaners as the spatial mode and noise filter of the laser at 1.55 μm and 775 nm,the squeezed vacuum of up to 3.0 dB below the shot noise level at 1.55 μm is experimentally obtained.This system is compatible with standard telecommunication optical fibers,and will be useful for continuous variable long-distance quantum communication and distributed quantum computing.